2016
DOI: 10.1155/2016/2019643
|View full text |Cite
|
Sign up to set email alerts
|

Magnesium Supplementation Diminishes Peripheral Blood Lymphocyte DNA Oxidative Damage in Athletes and Sedentary Young Man

Abstract: Sedentary lifestyle is highly associated with increased risk of cardiovascular disease, obesity, and type 2 diabetes. It is known that regular physical activity has positive effects on health; however several studies have shown that acute and strenuous exercise can induce oxidative stress and lead to DNA damage. As magnesium is essential in maintaining DNA integrity, the aim of this study was to determine whether four-week-long magnesium supplementation in students with sedentary lifestyle and rugby players co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 44 publications
2
21
0
1
Order By: Relevance
“…Therefore, this study provides further data that prove that the cor-relation found between the antioxidant status and DNA damage in the melatonin-treated group may explain the association between higher TAC and less DNA damage with melatonin supplementation. Evidence indicates that supplementation with other nutrients showed protective effects in reducing the level of H2O2-induced PBL DNA damage in physically active individuals [27]. The results from the comet assay combined with our results on antioxidant status suggest that the decrease in spontaneous DNA damage observed after training is most likely ascribable to melatonin supplementation.…”
Section: Parameters Placebo Group Melatonin Groupsupporting
confidence: 57%
“…Therefore, this study provides further data that prove that the cor-relation found between the antioxidant status and DNA damage in the melatonin-treated group may explain the association between higher TAC and less DNA damage with melatonin supplementation. Evidence indicates that supplementation with other nutrients showed protective effects in reducing the level of H2O2-induced PBL DNA damage in physically active individuals [27]. The results from the comet assay combined with our results on antioxidant status suggest that the decrease in spontaneous DNA damage observed after training is most likely ascribable to melatonin supplementation.…”
Section: Parameters Placebo Group Melatonin Groupsupporting
confidence: 57%
“…Iron Involved in regulation of cytokine production and action [3]; required for generation of pathogen-killing ROS by neutrophils during oxidative burst [7] Copper Accumulates at sites of inflammation [7,35]; part of copper/zinc-superoxide dismutase, a key enzyme in defense against ROS [8]; free-radical scavenger [58]; changes in copper homeostasis a crucial component of respiratory burst [8]; important for IL-2 production and response [7,35]; maintains intracellular antioxidant balance, suggesting important role in inflammatory response [8] Selenium Essential for function of selenoproteins that act as redox regulators and cellular antioxidants, potentially counteracting ROS produced during oxidative stress [2] Magnesium Can help to protect DNA against oxidative damage [37]; high concentrations reduce superoxide anion production [59] Differentiation, proliferation and normal functioning of T cells Vitamin A Involved in development and differentiation of Th1 and Th2 cells [60]; enhances TGF-β-dependent conversion of naïve T cells into regulatory T cells [8]; plays a role in acquisition of mucosal-homing properties by T and B cells [8] Vitamin D Homing of T cells to the skin [61]; calcitriol inhibits T-cell proliferation [7]; inhibitory effects mainly in adaptive immunity (e.g., Th1-cell activity) [7]; stimulatory effects in innate immunity [7]; inhibits the effector functions of T helper cells and cytotoxic T cells [27,62], but promotes the production of Tregs [27,62,63]; inhibitory effect on the differentiation and maturation of the antigen-presenting DCs, and helps program DCs for tolerance [27,[64][65][66] Vitamin C Roles in production, differentiation, and proliferation of T cells, particularly cytotoxic T cells [3,21] Vitamin E Enhances lymphocyte proliferation and T-cell-mediated functions [3]; optimizes and enhances Th1 response [3] Vitamin B6 Involved in lymphocyt...…”
Section: Immune Function Roles Micronutrient Commentsmentioning
confidence: 99%
“…Through a Fenton-like reaction, copper can also catalyze the formation of ROS and is thus used to kill pathogens [8,90], while it also acts as a free-radical scavenger [58]. Magnesium helps to protect DNA against oxidative damage and is involved in the regulation of apoptosis [37].…”
Section: Natural Killer Cells and Phagocytesmentioning
confidence: 99%
See 1 more Smart Citation
“…Дотации магния (400 мг/сут, 4 нед.) снижали окислительное повреждение лимфоцитов периферической крови у регбистов [71]: спортсмены характеризовались значительно меньшими общими количествами клеток с повреждениями ДНК в присутствии H 2 O 2 по сравнению с контрольной группой (p = 0,002, рис. 13).…”
Section: магний и иммунитет у спортсменовunclassified